TP63 and TP73 in cancer, an unresolved "family" puzzle of complexity, redundancy and hierarchy. Issue 16 (28th June 2014) - Costanzo, Antonio; Pediconi, Natalia; Narcisi, Alessandra; Guerrieri, Francesca; Belloni, Laura; Fausti, Francesca; Botti, Elisabetta; Levrero, Massimo
Abstract : TP53 belongs to a small gene family that includes, in mammals, two additional paralogs, TP63 and TP73 . The p63 and p73 proteins are structurally and functionally similar to p53 and their activity as transcription factors is regulated by a wide repertoire of shared and unique post‐translational modifications and interactions with regulatory cofactors. p63 and p73 have important functions in embryonic development and differentiation but are also involved in tumor suppression. The biology of p63 and p73 is complex since both TP63 and TP73 genes are transcribed into a variety of different isoforms that give rise to proteins with antagonistic properties, the TA‐isoforms that act as tumor‐suppressors and DN‐isoforms that behave as proto‐oncogenes. The p53 family as a whole behaves as a signaling "network" that integrates developmental, metabolic and stress signals to control cell metabolism, differentiation, longevity, proliferation and death. Despite the progress of our knowledge, the unresolved puzzle of complexity, redundancy and hierarchy in the p53 family continues to represent a formidable challenge.